Pathogenic mutations in neurofibromin identifies a leucine-rich domain regulating glioma cell invasiveness - Fadhlullah, Siti Farah Bte; Halim, Nurashikin Bte Abdul; Yeo, Jacqueline Y. T.; Ho, Rachel L. Y.; Um, Phoebe; Ang, Beng Ti; Tang, Carol; Ng, Wai H.; Virshup, David M.; Ho, Ivy A. W. (Oncogene, 2019)
Glioblastoma (GBM) is the most aggressive tumor of the brain. NF1 , a tumor suppressor gene and RAS-GTPase, is one of the highly mutated genes in GBM. Dysregulated NF1 expression promotes cell invasion, proliferation, and tumorigenesis. Loss of NF1 expression in glioblastoma is associated with increased aggressiveness of the tumor. Here, we show that NF1 -loss in patient-derived glioma cells using shRNA increases self-renewal, heightens cell invasion, and promotes mesenchymal subtype and epithelial mesenchymal transition-specific gene expression that enhances tumorigenesis. The neurofibromin protein contains at least four major domains, with the GAP-related domain being the most well-studied. In this study, we report that the leucine-rich domain (LRD) of neurofibromin inhibits invasion of human glioblastoma cells without affecting their proliferation. Moreover, under conditions tested, the NF1-LRD fails to hydrolyze Ras-GTP to Ras-GDP, suggesting that its suppressive function is independent of Ras signaling. We further demonstrate that rare variants within the NF1-LRD domain found in a subset of the patients are pathogenic and reduce NF1-LRD’s invasion suppressive function. Taken together, our results show, for the first time, that NF1-LRD inhibits glioma invasion, and provides evidence of a previously unrecognized function of NF1-LRD in glioma biology.